CROSS-SECTION STUDIES: ADVANTAGES AND DISADVANTAGES - Grujicic, Sandra; Nikolic, Aleksandra (HEALTH CARE, 2021)
The cross-sectional study belongs to the group of observational studies. Some authors classify cross-sectional studies as analytical studies and others as descriptive studies. The names for this study are both the prevalence study and the transversal study. In this study, the exposure to risk factors and the existence of the disease is determined simultaneously. These studies are a “snapshot” of the current situation. They are most suitable for public health planning, etiological testing, and diagnostic testing. They are not used for research on short-term diseases and rare health disorders, and their main drawback is that the direction of the cause-and-effect relationship cannot be determined. On the other hand, these studies are cheaper, faster, and easier to perform and do not scatter data compared to cohort studies, and compared to case studies and controls, they are performed on a representative sample, and there is no recall bias regarding exposure to risk factors.
Keywords: cross-sectional study, advantages, disadvantages, odds ratio